Infrastructure and public-private partnerships in Latin America and the Caribbbean - Bloomgarden, David R. (Multilateral Investment Fund [Washington]US, 2008)
Discusses IMF support for infrastructure development in the region, emphasizing the promotion of public-private partnerships.